Strategy for Information Literacy Development: Management Undergraduate Program at U.S. Coast Guard Academy - Zapalska, Alina M; McCarty, Mike (Advances in Social Sciences Research Journal, 2017)
The paper presents an integrated approach of teaching and assessing information literacy at the United States Coast Guard Academy, with specific examples from the Management Program. The success of information literacy at United States Coast Guard Academy is based on the Indiana University framework, a successful collaborative environment, and a new core curriculum that uses a threading approach to expand IL development across disciplines and throughout the four-year curriculum. The future success of IL at CGA will depend on regular assessment and improvement of student development in this critical skill that is essential for success in college, in career advancement, and in life.